Ruptures and resurgences: Marking the spatiality of transgender identity in India since the enactment of Transgender Persons Act 2019 - Gupta, Nikhil K. (Frontiers in Political Science, 2022)
Transgender groups in India constitute an indigenous community with a rich and vivid culture and history. However, it is unfortunate that under the hegemonic influence of heteronormative traditions, the democratic inclusion and accommodation of transgender groups could never take place. This exclusion and neglect have recently been challenged through the activism of several groups, which has given rise to a new chapter in the democratic unfolding in India. This article attempts to evaluate the social activism of transgender groups on two planes. One plane attempts to evaluate it in terms of the uniqueness of an indigenous social movement and the areas that distinguish it from other social movements. It is interesting to note that what started as a purely identity-based social movement has now acquired dimensions of redistributive justice. The second plane attempts to evaluate the social activism of transgender groups in terms of the achievements and advances made by the movement on the social and political fronts. This evaluation is necessary in order to appraise the trajectory of the politics of transgender groups, which could foretell the direction of the activism and help in understanding the future scope and direction. The article takes up three arguments in the context of the legal framework put in effect by the state. The first point of discussion is the effectiveness of the transgender ID provided by the Transgender Persons Act and the possible challenges and loopholes related to it. While the state provides legal recognition through the issuance of the transgender ID card, it only remains a symbolic marker as the de facto identity remains unchanged, unless changed by the person themselves. The second point of discussion is the emerging rift amongst transgender groups with respect to the reforms introduced recently. This rift has a tendency to pull in the opposite direction, causing tensions. The final aspect of my discussion relates to the subsequent challenges that emerge from the legal recognition of transgender persons. These challenges touch upon the various aspects of legal, political, social, and economic policymaking and are inevitable for understanding the concerns of transgender persons in India.